High-quality Ti(C, N)-based cermets via solid-state nitrogen-pressure sintering: Influence of the sintering atmosphere. (November 2020) - Chu, Shenglin; Liu, Gang; Xiong, Huiwen; Li, Zhiyou; Zhou, Kechao
Abstract: Owing to the denitrification behavior of Ti(C, N)-based cermets during the sintering process, nitrogen atmosphere sintering is essential for the fabrication of high-quality products. Disclosing the roles of the sintering atmosphere on the microstructure and properties of cermet is of significance. Herein, Ti(C, N)-based cermets were fabricated under six types of sintering atmosphere. Effects of sintering atmosphere on the microstructure, coercive force (Hc), specific saturation magnetization (Ms (%)), and mechanical properties of cermets were investigated. More rimless Ti(C, N) grains with increased fraction of black cores were formed with increasing the nitrogen partial pressure. Three types of gradient structure of cermets were confirmed caused by the different nitrogen activity at the liquid sintering state. Vacuum sintering induced the formation of thicker rims on smaller Ti(C, N) cores at the surface due to the low nitrogen potential, while fcc solid solutions rich in N was formed in nitrogen atmosphere. Vacuum sintered cermets showed the lowest Hc and Ms. (%) of 3.66 KA/m and 2.13%, owing to the denitrification process. High-quality Ti(C, N)-based cermets were achieved via the solid-state nitrogen atmosphere sintering, benefiting from the optimized core-rim structure, i.e. moderate thickness of rims and certain amount of black Ti(C, N) cores. Highlights: Influence of the sintering atmosphere on the microstructure and properties of cermet is investigated. Three types of gradient structure of cermets were clarified due to different nitrogen activity. High-quality Ti(C, N)-based cermets were achieved via the solid-state nitrogen-pressure sintering.